Sebab-sebab Historis Lahirnya Metode Maudu’i dalam Tafsir - Irsyad Al Fikri Ys; Deden Rohmanudin (Jurnal Iman dan Spiritualitas, 2021)
The Qur'an, as a revelation revealed to the Prophet Muhammad SAW., has various types of high-value science, so that many researchers want to uncover the contents of the Qur'an. Departing from this, the purpose of writing this article is to find out the history of the emergence of maudu’i interpretation. The method used in writing this article uses library research by collecting primary and secondary data. The results of this article show that the history and factors behind the emergence of maudu’i interpretations are due to a lack of concern in the past to interpret the Qur'an thematically. Then along with the development of the times, it is necessary to pay attention to analyzing the Qur'an with specific topics as a form of an answer to the challenges of the times.